2012
DOI: 10.1073/pnas.1200484109
|View full text |Cite
|
Sign up to set email alerts
|

Janus-faced liposomes enhance antimicrobial innate immune response in Mycobacterium tuberculosis infection

Abstract: We have generated unique asymmetric liposomes with phosphatidylserine (PS) distributed at the outer membrane surface to resemble apoptotic bodies and phosphatidic acid (PA) at the inner layer as a strategy to enhance innate antimycobacterial activity in phagocytes while limiting the inflammatory response. Results show that these apoptotic body-like liposomes carrying PA (ABL/ PA) (i) are more efficiently internalized by human macrophages than by nonprofessional phagocytes, (ii) induce cytosolic Ca 2+ influx, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 59 publications
0
68
0
1
Order By: Relevance
“…The prolonged and complex anti-TB chemotherapy for MDR-and XDR-TB cases includes antibiotics that are very expensive. For instance, combining direct and indirect costs, the average cost per-TB case in the original EU states was estimated at 10.282 EUR for drug susceptible TB, 57,213 EUR for MDR-TB and 170,744 EUR for XDR-TB, with a total cost for TB treatment in Europe surpassing the 0.5 billion EUR in 2011 [3]. Hence, the emergence of drug resistance is posing a major threat to control TB, with important health, social and economic consequences [2].…”
mentioning
confidence: 99%
“…The prolonged and complex anti-TB chemotherapy for MDR-and XDR-TB cases includes antibiotics that are very expensive. For instance, combining direct and indirect costs, the average cost per-TB case in the original EU states was estimated at 10.282 EUR for drug susceptible TB, 57,213 EUR for MDR-TB and 170,744 EUR for XDR-TB, with a total cost for TB treatment in Europe surpassing the 0.5 billion EUR in 2011 [3]. Hence, the emergence of drug resistance is posing a major threat to control TB, with important health, social and economic consequences [2].…”
mentioning
confidence: 99%
“…If the diagnosis and treatment of bone tuberculosis is not timely, it can cause spinal deformity, limited activity, and even paraplegia, seriously affecting the quality of life of the patients. Mycobacterium tuberculosis invades the body and multiplies in cells and causes an inflammatory response and therefore, disrupts the function of the immune system [29]. The immune mechanism of the host cells, thus plays an important role in the growth of Mycobacterium tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies utilizing these phosphatidic acid-loaded liposomes in TB-infected mice demonstrated their ability to induce heightened immunological responses, increase reactive oxygen species levels within phagolysosomes and facilitate intracellular mycobacterial killing within macrophages. [33] …”
Section: Liposomes As Drug Delivery Systemsmentioning
confidence: 99%